Composite material for absorbing shock waves and manufacturing method thereof
A composite material with a polymer matrix, fiber reinforcement, and surface-dispersed absorbing particles addresses the trade-off between mechanical properties and shock wave absorption, maintaining strength while enhancing damping performance.
Patent Information
- Application Number
- KR1020240016133
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-02-01
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2044-02-01
AI Technical Summary
Existing fiber-reinforced plastics (FRP) face a trade-off between mechanical properties and shock wave absorption performance, where improving one often deteriorates the other, necessitating a composite material that balances both.
A shock wave absorbing composite material with a polymer matrix, fiber reinforcement, and shock wave absorbing particles dispersed on the upper surface layer, manufactured via a Multi-Drop Filling (MDF) process, ensuring optimal distribution and minimal interfacial delamination.
The composite material achieves high shock wave damping without degrading mechanical properties by concentrating absorbing particles on the surface layer, effectively attenuating initial shock waves and preventing internal delamination.
Smart Images

Figure 112024013134079-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a fiber-reinforced composite material for shock wave attenuation. Background Technology
[0002] The importance of preventing and responding to safety accidents related to explosions is growing in sectors such as civilian businesses and the defense industry, where explosives are used or there is a risk of exposure to explosions. As explosive power increases alongside scientific advancements, damage caused by explosions is now occurring not only from fragments but also from shock waves.
[0003] In particular, bulletproof helmets and vests used in the defense sector require high mechanical properties and ballistic protection, and various products are being developed to meet these requirements. Occupations with high exposure to explosions, especially soldiers, frequently suffer from conditions such as traumatic brain injury caused by shock waves generated by blasts. Therefore, the shock wave protection performance of explosion-related safety equipment is becoming increasingly important.
[0004] Fiber reinforced plastic (FRP) is a composite material composed of a polymer matrix and fiber reinforcements. Due to its excellent specific strength, it is used as a substitute for metal materials; in particular, aramid fiber reinforced plastic (AFRP), which uses aramid fibers as reinforcements, is currently utilized in bulletproof helmets and vests.
[0005] Recently, active research is being conducted to develop optimal FRP structures by considering the types of resins and fibers and introducing various shock-absorbing materials to achieve excellent mechanical properties and shock wave protection performance. Since shock-absorbing materials generally possess flexible characteristics, they exhibit superior shock wave absorption performance due to their damping effect. However, because this conflicts with the mechanical properties (strength, stiffness, etc.) of the FRP, a problem exists regarding a trade-off relationship between the composition of the shock-absorbing material and its properties. For example, if mechanical properties are improved by increasing the specific gravity of the FRP, the specific gravity of the shock-absorbing material decreases, leading to a reduction in shock wave absorption performance; conversely, if the specific gravity of the shock-absorbing material is increased, the overall mechanical properties of the FRP may be weakened by the properties of the shock-absorbing material itself.
[0006] Therefore, there is a need for technology to manufacture composite materials that minimize trade-offs between material properties and possess excellent mechanical properties and shock wave damping capabilities. The problem to be solved
[0007] One objective of the present invention is to provide a shock wave absorbing composite material having excellent mechanical properties and superior shock wave absorption performance.
[0008] Another objective of the present invention is to provide a method for manufacturing a shock wave absorbing composite material having an optimal integrated structure and excellent mechanical properties and shock wave damping ability by controlling the distribution of shock wave absorbing particles. means of solving the problem
[0009] In one aspect, the present invention provides a shock wave absorbing composite material comprising a polymer matrix, fiber reinforcement laminated within the polymer matrix, and shock wave absorbing particles dispersed on the upper surface layer of the polymer matrix.
[0010] In one embodiment, the polymer matrix may include one or more selected from epoxy resin, ester resin, phenolic resin, polyamide, polyvinyl chloride, and polyether ether ketone.
[0011] In one embodiment, the fiber reinforcement may include one or more selected from carbon fibers, aramid fibers, glass fibers, boron fibers, basalt fibers, and CNT fibers.
[0012] In one embodiment, the shock wave absorbing particles may include one or more selected from silicone rubber, PDMS, polyurethane, and polyurea.
[0013] In one embodiment, the shock wave absorbing particles may be included in an amount of 0.1 wt% or more and less than 25 wt% relative to the weight of the polymer matrix.
[0014] In another aspect, the present invention provides a method for manufacturing a shock wave absorbing composite material comprising the steps of impregnating a laminated fiber reinforcement with a polymer resin, and manufacturing a composite material by applying and curing a suspension in which shock wave absorbing particles are dispersed in a polymer resin onto the fiber reinforcement through a Multi-Drop Filling (MDF) process.
[0015] In one embodiment, the temperature of the polymer resin may be greater than 40°C and less than 120°C.
[0016] In one embodiment, a suspension in which shock wave absorbing particles are dispersed in a polymer resin can be prepared such that the shock wave absorbing particles are included in an amount of 0.1 wt% or more and less than 25 wt% relative to the total weight of the polymer resin.
[0017] In one embodiment, the suspension in which shock wave absorbing particles are dispersed in the polymer resin can be prepared by dispersing shock wave absorbing particles in the polymer resin and then performing a degassing treatment.
[0018] In one embodiment, the polymer resin comprises one or more selected from epoxy resin, ester resin, phenolic resin, polyamide, polyvinyl chloride, and polyether ether ketone, the fiber reinforcement comprises one or more selected from carbon fiber, aramid fiber, glass fiber, boron fiber, basalt fiber, and CNT fiber, and the shock wave absorbing particles may comprise one or more selected from silicone rubber, PDMS, polyurethane, and polyurea. Effects of the invention
[0019] The shock wave absorbing composite material according to the present invention can achieve a high shock wave damping effect without degrading the mechanical properties of the final composite material, because the shock wave absorbing particles are locally dispersed only in the upper surface layer of the composite material.
[0020] According to the method for manufacturing a shock wave-absorbing composite material of the present invention, by intensively distributing shock wave-absorbing particles only on the upper surface layer of the polymer matrix, the location where delamination occurs at the interface between the particles and the polymer matrix is minimized, thereby minimizing the degradation of mechanical properties. Furthermore, by maximizing the content of shock wave-absorbing particles distributed on the upper surface layer, the shock wave initially incident on the composite material can be effectively attenuated at an early stage. This effectively protects against the transmission of shock waves into the interior of the composite material, thereby preventing interfacial delamination between internal fiber layers caused by shock waves, which not only maintains durability but also enhances the safety of the wearer. Brief explanation of the drawing
[0021] FIG. 1 is a diagram showing the structure of a shock wave absorbing composite material according to an embodiment of the present invention. Figure 2 is a photograph showing the manufacturing process of a shock wave absorbing composite material according to an embodiment of the present invention in sequence. FIG. 3 is a schematic diagram showing the manufacturing process of a suspension in which shock wave absorbing particles are dispersed in a polymer resin according to an embodiment of the present invention. Figure 4 is a photograph showing a) a shock wave absorbing material in particle form, b) an epoxy suspension before particle dispersion, and c) an epoxy suspension after particle dispersion. Figure 5 is a schematic diagram showing an MDF process according to an embodiment of the present invention. FIG. 6 is a diagram showing the structure of a shock wave absorbing composite material according to Comparative Example 2 of the present invention. Figure 7 is a photograph showing an example in which an unimpregnated section is formed as the resin viscosity increases in Experimental Example 1 of the present invention. Figure 8 is a photograph showing the surface of a shock wave absorbing composite material prepared by adding 25 wt% PDMS in Experimental Example 2 of the present invention. Figure 9 shows a cross-sectional photograph of a shock wave absorbing composite material manufactured with a small amount of coating resin in Experimental Example 3 of the present invention. Figure 10 shows a cross-sectional photograph of a shock wave absorbing composite material manufactured with an excess amount of coating resin in Experimental Example 3 of the present invention. Figure 11 shows the results of measuring the tensile strength of Comparative Example 2 and Example 2 in a) and b) Example. Figure 12 a) Comparative Example 2 and b) Example are the results of measuring the impact strength related to the bulletproof properties. Figure 13 shows the results according to PDMS content, a) shock wave detected after shock wave attenuation, b) shock wave attenuation rate, and c) shock wave attenuation effect of epoxy / PDMS compared to epoxy. Figure 14 shows the results of evaluating the shock wave absorption performance of the material of Comparative Example 1 with a thickness of 500 μm and the material of Example with a thickness of 500 μm containing 20 wt% PDMS. Specific details for implementing the invention
[0022] Hereinafter, embodiments of the present invention will be described in detail with reference to the attached drawings. Since the present invention is susceptible to various modifications and may take various forms, specific embodiments are illustrated in the drawings and described in detail in the text. However, this is not intended to limit the present invention to the specific disclosed forms, and it should be understood that it includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the present invention. Similar reference numerals have been used for similar components in the description of each drawing. In the attached drawings, the dimensions of the structures are shown enlarged compared to the actual dimensions for the clarity of the present invention.
[0023] The terms used in this application are used merely to describe specific embodiments and are not intended to limit the invention. The singular expression includes the plural expression unless the context clearly indicates otherwise. In this application, terms such as "comprising" or "having" are intended to specify the presence of the features, numbers, steps, actions, components, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, or combinations thereof.
[0024] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which the present invention pertains. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in this application.
[0025] FIG. 1 is a diagram showing the structure of a shock wave absorbing composite material according to an embodiment of the present invention.
[0026] Referring to FIG. 1, a composite material (10) for shock wave absorption according to an embodiment of the present invention may include a polymer matrix (11), a fiber reinforcement (12), and shock wave absorption particles (13).
[0027] Fiber reinforcement (12) is laminated inside the polymer matrix (11), and shock wave absorbing particles (13) are dispersed on the upper surface layer.
[0028] In one embodiment, the polymer matrix (11) may include a thermosetting polymer or a thermoplastic polymer. As an example, the thermosetting polymer used as the material for the polymer matrix (11) may include epoxy resin, ester resin, phenolic resin, etc. More specifically, epoxy resin may be used, and depending on the application and structure, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol B type epoxy resin, bisphenol S type epoxy resin, novolak epoxy resin, etc. may be used. Generally, the thermosetting resin may be used by mixing it in a specific ratio with a curing agent such as an amine-based, acid anhydride-based, imidazole-based, or aromatic polyamine-based agent.
[0029] Meanwhile, the thermoplastic resin used as the polymer matrix (11) material may be, for example, polyamide, polyvinyl chloride, polyether ether ketone, etc.
[0030] The fiber reinforcement (12) is laminated within the polymer matrix (11) to strengthen the mechanical properties of the composite material.
[0031] In one embodiment, the fiber reinforcement (12) may include one or more types such as carbon fiber, aramid fiber, glass fiber, boron fiber, basalt fiber, CNT fiber, etc. The fiber reinforcement (12) is classified into plain weave, twill weave, satin weave, uni-direction, etc. depending on the fiber weaving, and since the physical properties differ depending on the direction, it can be appropriately selected according to the purpose. More specifically, plain weave aramid fiber may be used as the fiber reinforcement (12).
[0032] Shock wave absorbing particles (13) are dispersed on the upper surface layer of the polymer matrix (11).
[0033] In one embodiment, the shock wave absorbing particle (13) may be an elastomer-based polymer, examples of which include PDMS, silicone rubber, polyurethane, polyurea, etc. Elastomer polymers can absorb the energy of shock waves through damping caused by segment relaxation of rapid polymer chains, frictional interaction of microdomains composed of soft segments and hard segments, etc. In particular, a silicon network cross-linked with PDMS has a low glass transition temperature and thus has excellent shock wave energy absorption performance.
[0034] The shock wave absorbing composite material (10) of the present invention illustrated in FIG. 1 can minimize the deterioration of mechanical properties by concentrating the shock wave absorbing particles (13) only on the upper surface layer of the polymer matrix (11), thereby minimizing the location where delamination occurs at the interface between the particles (13) and the polymer matrix (11). In addition, by maximizing the content of the shock wave absorbing particles (13) distributed on the upper surface layer, the shock wave initially incident on the composite material (10) can be effectively attenuated. This effectively protects against the transfer of shock waves into the interior of the composite material (10), thereby preventing delamination at the interface between the internal fiber (12) layers caused by shock waves in the composite material (10), which not only maintains durability but also increases the safety of the wearer.
[0035] In one embodiment, the content of the shock wave absorbing particles (13) may be 0.1 wt% or more and less than 25 wt% relative to the weight of the polymer matrix (11). If the content is less than 0.1 wt%, the shock wave absorption effect may be negligible, and if the content is 25 wt% or more, the physical properties of the composite material may decrease due to interfacial separation with the polymer matrix, reduced processability, etc.
[0036] The structure of the shock wave absorbing composite material (10) of the present invention can be implemented by the following method (see FIG. 2).
[0037] A method for manufacturing a shock wave absorbing composite material according to one embodiment of the present invention may include the step of impregnating a laminated fiber reinforcement with a polymer resin (S110), and the step of manufacturing a composite material by applying and curing a suspension in which shock wave absorbing particles are dispersed in a polymer resin onto the fiber reinforcement through a Multi-Drop Filling (MDF) process (S120).
[0038] Step S110 above includes the step of impregnating a laminated fiber reinforcement with a polymer resin. In one embodiment, the polymer resin may include a thermosetting polymer or a thermoplastic polymer, and the type thereof may be used as described above. More preferably, the polymer resin may be an epoxy resin. Step S120 above includes the step of manufacturing a composite material by applying and curing a suspension in which shock wave absorbing particles are dispersed in a polymer resin onto the fiber reinforcement through a Multi-Drop Filling (MDF) process.
[0039] In one embodiment, the suspension in which shock wave absorbing particles are dispersed in the polymer resin can be prepared by dispersing shock wave absorbing particles in the polymer resin and then performing a degassing treatment. Specifically, the dispersion process may sequentially use a high shear mixer and a speed mixer, and the degassing process may use a vacuum oven.
[0040] More specifically, referring to Fig. 3, a mixture in which particulate shock wave absorbing material is added to a polymer resin is dispersed using a high shear mixer. Here, the polymer resin may be an epoxy resin. Since the dispersion contains a large amount of bubbles due to the high RPM characteristic of the high shear mixer, the gas present in the polymer resin can be removed through a degassing process. In the degassing step, the shock wave absorbing particles that rise due to the density difference are redispersed using a speed mixer, thereby preparing a suspension in which shock wave absorbing particles are dispersed in the polymer resin (see Fig. 4).
[0041] Meanwhile, referring to FIG. 5, the Multi-Drop Filling (MDF) process is a novel automated manufacturing process technology based on 3D printing that can apply a specified amount of resin to a designated location. In the present invention, a composite material can be manufactured by applying a suspension in which shock wave absorbing particles are dispersed in a polymer resin onto the fiber reinforcement in a specified amount to a designated location and curing the polymer resin. The suspension of the present invention forms a high viscosity, and since the MDF process can apply a specified amount of resin by controlling pressure and time, it is advantageous for using high-viscosity resin compared to other conventional processes.
[0042] The quantity of resin to be used in the MDF process can be determined by the resin viscosity, application pressure, and time. Therefore, process factors ranging from the resin temperature and the content of shock wave-absorbing particles to the application pressure and time may be considered. In particular, when using epoxy resin, which is a thermosetting resin, in the present invention, it exhibits curing behavior depending on temperature and time. Since this is closely related to the resin's pot life (the time during which the resin can flow before its viscosity rises above a certain level due to curing) and temperature, it is important to control these factors appropriately. Resins at low temperatures (40°C or lower) have high viscosity and a slow impregnation rate, while at high temperatures (120°C or higher), curing behavior proceeds rapidly, causing a sharp increase in viscosity that may render the process impossible. Therefore, it is preferable that the temperature of the polymer resin be greater than 40°C and less than 120°C.
[0043] In addition, the weight fraction of the shock wave absorbing particles may be proportional to the shock wave attenuation rate. In terms of shock wave protection, it is desirable to add as much shock wave absorbing particle as possible; however, the properties of the composite material may be reduced due to the inherently low physical properties of the material, interfacial separation with the polymer matrix, and reduced processability. Furthermore, if an excessive amount of shock wave absorbing particles is included, dispersibility may be low during the processing and aggregation may occur on the surface. Therefore, it is desirable that the shock wave absorbing particles be included in an amount of at least 0.1 wt% and up to 25 wt% relative to the total weight of the polymer resin.
[0044] The method for manufacturing a shock wave-absorbing composite material according to the present invention manufactures an integrated shock wave-absorbing composite material in which shock wave-absorbing particles exist within the matrix rather than being coated on the outside of the matrix. By concentrating the distribution of shock wave-attenuating particles on the outermost layer of the composite material to form a shock wave absorption layer, most of the initial shock wave can be absorbed. This structure maximizes the shock wave absorption performance of the composite material while minimizing the positioning between the fiber reinforcement and the resin, thereby preventing delamination of heterogeneous interfaces that occur during shock wave attenuation and preventing the deterioration of the mechanical properties of the composite material.
[0045] The embodiments of the present invention are described in detail below. However, the embodiments described below are merely partial embodiments of the present invention, and the scope of the present invention is not limited to the following embodiments.
[0046] Examples
[0047] After laminating plain-weave aramid fibers, epoxy resin was applied to impregnate the laminated fiber reinforcement (Step 1). Next, an epoxy suspension containing shock wave absorbing particles (PDMS) at concentrations of 0.1, 0.2, 1, 2, 5, 10, and 20 wt% was applied to the top of the fiber reinforcement via a Multi-Drop Filling (MDF) process, followed by compression and curing (Step 2) to prepare a fiber-reinforced composite material with the structure of Fig. 1 (hereinafter referred to as Shock Wave Particle Content-AFRP).
[0048] Comparative Example 1
[0049] A plain weave aramid fiber reinforced composite material (fiber reinforced plastic) without added shock wave absorbing particles was prepared (hereinafter referred to as AFRP).
[0050] Comparative Example 2
[0051] After laminating plain weave aramid fibers, an epoxy suspension containing shock wave absorbing particles (PDMS) at concentrations of 0.1, 0.2, 1, and 2 wt%, respectively, was applied and impregnated onto the laminated fiber reinforcement, and compression and curing were performed to prepare a fiber-reinforced composite material with the structure of Fig. 6 (hereinafter referred to as Shock Wave Particle Content-AFRP).
[0052] Experimental Example 1
[0053] In the example for manufacturing a fiber-reinforced composite material of the structure of Fig. 1, the temperature and process time of the epoxy resin are important factors because the lower the viscosity of the polymer resin, the more advantageous the MDF process and impregnation are. Resins at low temperatures (40°C or lower) have high viscosity and slow impregnation rates, while resins at high temperatures (120°C or higher) undergo rapid curing behavior, causing a sharp increase in viscosity that may make the process impossible. Similar defects occur in epoxy resins with added shock wave absorbing particles due to an increase in viscosity caused by particle addition; furthermore, the slow impregnation rate and rapid curing behavior caused by the addition of shock wave absorbing particles can lead to the occurrence of unimpregnated sections and phase separation in the composite material, as shown in Fig. 7. Therefore, it is preferable that the temperature of the epoxy resin be greater than 40°C and less than 120°C.
[0054] Experimental Example 2
[0055] In the example for manufacturing a fiber-reinforced composite material of the structure of Fig. 1, if the content of PDMS, which is a shock wave absorbing particle, is 25 wt% or more, the viscosity of the epoxy / PDMS suspension increases, and wettability decreases, so as shown in Fig. 8, not only does it not spread on the structure, but dispersibility is also low and aggregation may occur on the surface. Therefore, it is preferable that the content of the shock wave absorbing particle be 0.1 wt% or more and less than 25 wt%.
[0056] Experimental Example 3
[0057] In an example for manufacturing a fiber-reinforced composite material of the structure of Fig. 1, in the first step, a fixed amount of epoxy resin is applied and impregnated to fill A% of the volume of the composite material, and then in the second step, a fixed amount of resin (epoxy / PDMS suspension) is applied and cured to fill (100-A)% of the volume of the composite material. Depending on A, the concentration of the epoxy / PDMS suspension and the degree of particle distribution within the composite material can be determined.
[0058] When a small amount of resin (26 ml or less) is applied in the first stage, the resin of the second stage spreads into the unimpregnated areas, which can act as a factor that expands the range of particle distribution (see Fig. 9). On the other hand, when an excessive amount of resin (30 ml or more) is applied in the first stage, most of the fibers are filled, and the resin of the second stage is squeezed rather than impregnated, which can cause a problem where a large amount of particles escape to the outside of the composite material (see Fig. 10). That is, the amount of resin applied in the first stage can be appropriately set to be greater than 26 ml and less than 30 ml.
[0059] Experimental Example 4
[0060] Evaluation of mechanical properties
[0061] The mechanical properties of the Examples, Comparative Examples 1 and 2 were compared, and the results are shown in FIGS. 11 and 12. FIG. 11 shows the results of measuring tensile strength (a-Comparative Example 2, b-Example), and FIG. 12 shows the results of measuring impact strength related to bulletproof properties (a-Comparative Example 2, b-Example).
[0062] As a result, Comparative Example 2 of the structure in Fig. 6 showed a decrease in tensile properties due to the influence of interfacial delamination between the particles and the epoxy as the rubber particle content increased. Although the impact strength also showed a decreasing trend as the particle content increased, it exhibited a relatively higher impact strength compared to Comparative Example 1 by attenuating the impact energy with the rubber particles.
[0063] On the other hand, in the embodiment of the structure of Fig. 1, mechanical properties (tensile strength, impact strength) similar to Comparative Example 1 were maintained because rubber particles were locally present only on the upper part of the composite material.
[0064] The composite material of the structure of Fig. 1 according to an embodiment of the present invention does not impair tensile strength and impact strength, and shock wave absorbing particles locally concentrated on the upper part have the characteristic of effectively attenuating the initially incident shock wave.
[0065] Evaluation of shock wave attenuation changes
[0066] The shock wave absorption performance of the composite material according to the content of shock wave absorbing particles (PDMS) was confirmed and is shown in Fig. 13. Since shock waves are sensitive to thickness, the shock wave absorption performance of the example according to the structure was indirectly evaluated by measuring the shock wave absorption performance of the matrix of the surface layer of the composite material that first contacts the shock wave.
[0067] Shock wave absorption performance was evaluated using a film prepared with a 50 μm epoxy suspension, which was considered as the epoxy / PDMS matrix layer formed on top of the composite material to which the shock wave first comes into contact.
[0068] As a result, it was confirmed through Figure 13a that the detected shock wave pressure decreases with increasing PDMS content, proving that PDMS has shock wave absorption performance even in particle form.
[0069] Figure 13b is a graph showing the pressure of the attenuated shock wave relative to the pressure of the incident shock wave, and Figure 13c confirms that at the maximum PDMS content of the composite material, 27 wt%, the shock wave absorption capacity is improved by 47% compared to an epoxy film without PDMS.
[0070] Meanwhile, to verify the shock wave attenuation rate of the composite material with actual PDMS embedded therein, the shock wave absorption performance of the material of Comparative Example 1 with a thickness of 500 μm and the material of Example 1 with a thickness of 500 μm containing 20 wt% PDMS was evaluated, and the results are shown in Fig. 14.
[0071] As shown in Fig. 14, the composite material of the example (Epoxy+AFRP+PDMS (20wt%)) showed a shock wave attenuation rate of approximately 38.6% compared to Comparative Example 1 (Epoxy+AFRP), and the composite material showed a difference in attenuation rate of approximately 39% due to PDMS. Through these results, the shock wave absorption performance of the composite material according to the embodiment of the present invention was proven.
[0072] Although the present invention has been described above with reference to preferred embodiments, those skilled in the art will understand that various modifications and changes can be made to the invention without departing from the spirit and scope of the invention as set forth in the following claims.
Claims
Claim 1 delete Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 A method for manufacturing a shock wave absorbing composite material comprising: a step of impregnating a laminated fiber reinforcement with a polymer resin; and a step of manufacturing a composite material by applying and curing a suspension in which shock wave absorbing particles are dispersed in a polymer resin onto the fiber reinforcement through a Multi-Drop Filling (MDF) process. Claim 7 A method for manufacturing a shock wave absorbing composite material according to claim 6, wherein the temperature of the polymer resin is greater than 40℃ and less than 120℃. Claim 8 A method for manufacturing a shock wave absorbing composite material according to claim 6, wherein a suspension in which shock wave absorbing particles are dispersed in a polymer resin is prepared such that the shock wave absorbing particles are included in an amount of 0.1 wt% or more and less than 25 wt% relative to the total weight of the polymer resin. Claim 9 In claim 6, the method for manufacturing a shock wave absorbing composite material is such that the suspension in which shock wave absorbing particles are dispersed in the polymer resin is prepared by dispersing shock wave absorbing particles in the polymer resin and then performing a degassing treatment. Claim 10 A method for manufacturing a shock wave absorbing composite material according to claim 6, wherein the polymer resin comprises one or more selected from epoxy resin, ester resin, phenolic resin, polyamide, polyvinyl chloride, and polyether ether ketone, the fiber reinforcing material comprises one or more selected from carbon fiber, aramid fiber, glass fiber, boron fiber, basalt fiber, and CNT fiber, and the shock wave absorbing particles comprise one or more selected from silicone rubber, PDMS, polyurethane, and polyurea.
Citation Information
Patent Citations
Compound bulletproof plate
JP2008162164A
Light emitting device
KR1020090132942A
